Costs and effects of paliperidone extended release compared with alternative oral antipsychotic agents in patients with schizophrenia in Greece: A cost effectiveness study - Papanicolaou Sotiria; Athanasakis Kostas; Ollandezos Markos; Kousoulakou Hara; Geitona Maria; Kyriopoulos Ioannis (Annals of General Psychiatry, 2008)
Abstract Background To compare the costs and effects of paliperidone extended release (ER), a new pharmaceutical treatment for the management of schizophrenia, with the most frequently prescribed oral treatments in Greece (namely risperidone, olanzapine, quetiapine, aripiprazole and ziprasidone) over a 1-year time period. Methods A decision tree was developed and tailored to the specific circumstances of the Greek healthcare system. Therapeutic effectiveness was defined as the annual number of stable days and the clinical data was collected from international clinical trials and published sources. The study population was patients who suffer from schizophrenia with acute exacerbation. During a consensus panel of 10 psychiatrists and 6 health economists, data were collected on the clinical practice and medical resource utilisation. Unit costs were derived from public sources and official reimbursement tariffs. For the comparators official retail prices were used. Since a price had not yet been granted for paliperidone ER at the time of the study, the conservative assumption of including the average of the highest targeted European prices was used, overestimating the price of paliperidone ER in Greece. The study was conducted from the perspective of the National Healthcare System. Results The data indicate that paliperidone ER might offer an increased number of stable days (272.5 compared to 272.2 for olanzapine, 265.5 f risperidone, 260.7 for quetiapine, 260.5 for ziprasidone and 258.6 for aripiprazole) with a lower cost compared to the other therapies examined (€7,030 compared to €7,034 for olanzapine, €7,082 for risperidone, €8,321 for quetiapine, €7,713 for ziprasidone and €7,807 for aripiprazole). During the sensitivity analysis, a ± 10% change in the duration and frequency of relapses and the economic parameters did not lead to significant changes in the results. Conclusion Treatment with paliperidone ER can lead to lower total cost and higher number of stable days in most of the cases examined.